Development of a digital training for social and emotional competences for medical assistants in vocational education and training in Germany - Peters, Markus [Verfasser]; Tschöpe, Tanja [Verfasser]; Konheiser, Sebastian [Verfasser]; Raecke, Julia [Verfasser]; Schnitzler, Annalisa [Verfasser] (My University, 2023)
„This paper describes a digital training for social and emotional competences for prospective medical assistants (MAs) in Germany. Social and emotional competences (SEC) are necessary for the collaboration with colleagues as well as for the contact with clients, patients or customers. The German dual system of vocational education and training (VET) therefore considers them as essential parts of the profle of most training occupations. Nevertheless, few materials exist so far for the systematic training of these competences. In former studies three social and emotional competences have been identifed as essential for MAs: emotion regulation, perspective coordination and communication strategies. At the same time development needs have been identified for all of them. To address these needs the three hours online training programme SECOTrain (Social and Emotional Competence Training) has been developed, which ofers separate training sessions for all three competences. The aim of the paper is to depict how the fostering of social and emotional competences can be approached via a digital training, report our experiences with this endeavour and to discuss associated advantages as well as challenges and ways to deal with them. Digital formats ofer new possibilities and chances for education and training, as they facilitate access to the content in a standardized and efcient way. An independent processing of trainings is made possible, regardless of time and teacher. At the same time, this comes along with a risk of overstraining some learners, as problems of understanding or motivation may occur. SECOTrain transfers pedagogical ideas into the context of digital learning to reduce these risks as much as possible. Each of the three training sessions follows the principles of the Cognitive Apprenticeship approach and is inspired by existing theories and trainings. Video sequences of typical critical interaction situations serve as material for explanation, application and refection to support a strong practical orien tation. Efects of the training will be evaluated in a pretest–posttest-follow-up experimental design. The paper presents goals and content as well as methods, pedagogical principles and theoretical foundation of SECOTrain. Furthermore, results of a small pilot study are presented and discussed with regard to further adjusting the training to the needs of the target group. At the end, an outline of the planned evaluation is given.“ (authors‘ abstract; BIBB-Doku)
Keywords: S 6.4.5.2 Übrige Gesundheitsberufe (außer Ärzte und Apotheker); G 1.2.3 Qualifikationsentwicklungen; 370; 300; Medizinischer Fachangestellter; Berufsausbildung; Sozialkompetenz; emotionale Intelligenz; emotionale Intelligenz; Trainingsprogramm